(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Melasma is a chronic, acquired pigmentary condition characterized by symmetrical, blotchy, brownish facial pigmentation, primarily affecting women. Though not medically harmful, it significantly impacts quality of life, self-esteem, and psychosocial wellbeing. Conventional depigmenting agents such as hydroquinone, corticosteroids, and chemical peels are associated with adverse effects and limited long-term efficacy, thereby necessitating the exploration of safe and natural alternatives. Kumkumadi Oil, a classical Ayurvedic polyherbal formulation, has traditionally been employed for improving skin complexion and treating hyper pigmentary conditions. The study investigated the melanin inhibitory potential of Kumkumadi Oil against forskolin-induced melanogenesis in A375 melanoma cells and was assessed by MTT assay to determine safe concentrations. Forskolin was used to stimulate intracellular cAMP signaling and enhance melanin production. A375 cells were treated with Kumkumadi Oil at 250µg/mL and 500µg/mL, and intracellular melanin levels were quantified spectrophotometrically. Effects were compared with forskolin-induced untreated controls. Results demonstrated a dose-dependent reduction in melanin content, accompanied by significant inhibition of tyrosinase activity, without inducing cytotoxic effects on the tested cells. The study provides in vitro evidence that Kumkumadi Oil reduces forskolin-induced melanogenesis in human melanoma cells. The present conceptualization establishes a scientific basis for evaluating the efficacy of traditional Kumkumadi Oil in melasma and other hyper pigmentary conditions, highlighting its potential to surpass conventional synthetic chemical medicines as a safer and more sustainable therapeutic option.